2017
DOI: 10.1007/s10741-017-9604-9
|View full text |Cite
|
Sign up to set email alerts
|

Primary palliative care for heart failure: what is it? How do we implement it?

Abstract: Heart Failure (HF) is a chronic and progressive illness, which affects a growing number of adults and is associated with a high morbidity and mortality, as well as significant physical and psychological symptom burden on both patients with HF and their families. Palliative care is the multidisciplinary specialty focused on optimizing quality of life and reducing suffering for patients and families facing serious illness, regardless of prognosis. Palliative care can be delivered as (1) specialist palliative car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 78 publications
(73 reference statements)
0
44
0
16
Order By: Relevance
“…Despite radical advances in cardiac therapy, heart failure (HF) remains a chronic, progressive, and incurable pandemic affecting an estimated 5.7 million people in the United States and 26 million people worldwide. [1][2][3][4] Troubling projections estimate that by 2030, over 8 million people in the United States will be diagnosed with HF, compounding its prevalence by an astounding 46% increase. 2 Throughout the course of illness, patients with HF will face dramatic functional limitations, physical and psychological high-symptom burden, and an uncertain clinical trajectory placing great demands on the patient, caregivers, clinicians, and health-care system at large.…”
Section: Introductionmentioning
confidence: 99%
“…Despite radical advances in cardiac therapy, heart failure (HF) remains a chronic, progressive, and incurable pandemic affecting an estimated 5.7 million people in the United States and 26 million people worldwide. [1][2][3][4] Troubling projections estimate that by 2030, over 8 million people in the United States will be diagnosed with HF, compounding its prevalence by an astounding 46% increase. 2 Throughout the course of illness, patients with HF will face dramatic functional limitations, physical and psychological high-symptom burden, and an uncertain clinical trajectory placing great demands on the patient, caregivers, clinicians, and health-care system at large.…”
Section: Introductionmentioning
confidence: 99%
“…Están determinadas por la enfermedad que se sufre , son distintas si se está en la fase final de un cáncer, de una enfermedad neurodegenerativa o de un padecimiento cardiovascular (44). Actualmente las personas con enfermedad cardiovascular al final de la vida reciben menos cuidados paliativos, en relación a pacientes con enfermedad oncológica; sigue latente en el medio académico, científico y asistencial la necesidad de desarrollar conocimientos concretos para el cuidado de esta población específica, resultados similares a los de otros estudios abordados desde la medicina tales como el de Aguayo, Gelfman y Howlett et al (10,19,24).…”
Section: Discussionunclassified
“…It was observed that heart failure was the most common prior condition in our patients. Th is fact could be explained by heart failure being a complicated disease with high morbidity and mortality rates, affecting many physical and mental abilities of patients, thus making trauma common in this population 26 .…”
Section: Epo = Erythropoietinmentioning
confidence: 99%